Storia e analisi dell’esercizio di una sala parrocchiale. Il cinema Coassini nell’Italia tra gli anni Cinquanta e Settanta (Schermi. Storie e culture del cinema e dei media in Italia, 2024)
The article examines the Catholic “Coassini” cinema run to analyze its internal dynamics in the light of the processes that led to the exponential growth and subsequent decline of parish cinemas in Italy from the 1950s to the 1970s. Among these dynamics, it aims to shed light on the stages of the theater’s design, the reasons behind its technical and aesthetic modernization, and the management of its cinema run, including the relationships with small and large businesses and local and national institutions. The article adopts a microhistorical approach presenting the hypotheses and findings in the context of the period’s broader historical and cultural framework.